Family Digital Literacy for Character Building in Primary Education - mubarok, husni (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Coaching children in the family was proof of digital literacy that could be transmitted from parents to children especially for under 12 years old. The role of the family was very important in using the internet because children didn’t have technical skills, knowledge or emotions in accessing various information and entertainment. The purpose of this study were a) the basic concept of digital literacy, b) the basic concept of character building, and c) analysis of the family digital literacy for character building in primary education. The method used was library research with a qualitative approach. Data sources in this article were journals and books relating to family digital literacy on character building. The results of this study were 1) Digital literacy is the knowledge and skills to use digital media in finding, evaluating, making information, and using it in a healthy, wise, intelligent, accurate, and precise in establishing communication and interaction in daily life. 2) Character building is an educational process experienced by children from the values ​​of life, religion, and morals to have intelligence, personality and noble character. 3) Family digital literacy for character building in primary education by increasing the ability to think critically, creatively, and positively.